Leg raise can detect exercise-induced pulmonary arterial wedge pressure elevation. (25th November 2020) - Nakata, C; Goda, A; Takeuchi, K; Kikuchi, H; Inami, T; Soejima, K; Satoh, T
Abstract: Background: Exercise-induced elevation of pulmonary arterial wedge pressure (PAWP) may show preclinical or exercise-induced left ventricular diastolic dysfunction. Invasive hemodynamic assessment during provocative maneuvers, like exercise and volume challenge, in these patients allows greater sensitivity to diagnose or exclude HFpEF. The aim of this study was to examine how the leg raise, which is a simple way to increase preload, can detect exercise-induced PAWP elevation. Methods: Four hundred seventy-nine patients (60±14y.o, mean pulmonary arterial pressure (PAP) 19mmHg, PAWP 8mmHg, CTEPH /IPAH/CTD-PH/SOB unknown reason: 357/56/38/28pts) with near-normal PAP and normal PAWP at rest underwent symptom-limited exercise test using supine cycle ergometer with right heart catheter. Exercise-induced elevation in PAWP of over 20mmHg was defined as exercise-induced elevation group. Results: ΔPAWP (after leg raise - rest) in the exercise-induced elevation group was significantly higher (6.0±4.1 vs. 2.7±3.9mmHg, p<0.001, in the older (age≥60y.o) group (n=276); 3.4±3.5 vs. 1.9±3.4mmHg, p<0.001, in the younger (age<60y.o) group (n=203)) than that in the non-elevation group after legs raise for cycle ergometer exercise. The area under the ROC curve for ΔPAWP was 0.72 (95% CI: 0.65–0.78) in the older and 0.64 (95% CI: 0.53–0.75) in the younger. In the older, the cut-off value for detect exercise-induced PAWP elevation of ΔPAWP was 4mmHg, with 72% sensitivity and 58% specificity. On the other hand, in the younger, the cut-off value was 3mmHg, with 69% sensitivity and 59% specificity. Conclusion: Leg raise can easily detect occult left ventricular diastolic dysfunction. Funding Acknowledgement: Type of funding source: None